Philanthropic and impact investors: private sector engagement, hybridity and the problem of definition (2019)
Private sector engagement in education is typically conceptualised as the provision of education or education services by non-state private actors. It is, however, broader than this and tends to occur in four main areas, that is, the provision, financing, management and regulation of education, and increasingly, of ancillary education services by non-state private actors. They may work with varying degrees of independence from government/ public and/or other private/non-state actors. Non-state private actors in global education may be said to operate along a continuum of three main statuses. These include profit-oriented or commercially driven entities, of which some may be publicly listed while others may be privately held (Fielden & LaRocque, 2008). Others are oriented towards making a positive social impact without profit (e.g., may be registered as trusts or charities in their local contexts). Hybrid actors sit between the two, having both a profit and social impact motive.